2021
DOI: 10.1021/jacs.0c12564
|View full text |Cite
|
Sign up to set email alerts
|

Artificial Metalloproteins with Dinuclear Iron–Hydroxido Centers

Abstract: Dinuclear iron centers with a bridging hydroxido or oxido ligand form active sites within a variety of metalloproteins. A key feature of these sites is the ability of the protein to control the structures around the Fe centers, which leads to entatic states that are essential for function. To simulate this controlled environment, artificial proteins have been engineered using biotin− streptavidin (Sav) technology in which Fe complexes from adjacent subunits can assemble to form [Fe III −(μ-OH)−Fe III ] cores. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(15 citation statements)
references
References 83 publications
0
15
0
Order By: Relevance
“…Despite the ubiquitous nature of natural (μ-carboxylato)­diiron enzymes, there are few examples of incorporating such an active site into an ArM due to the difficulty involved in tailoring a binding environment for not one but two metal centers. The de novo Due Ferri (DF) scaffold designed by Lombardi, DeGrado, and co-workers has proven to be extremely valuable for the generation and study of such active sites and is discussed in depth by Pecoraro and co-workers. Recently, the Sav-biotin system was reengineered to form a unique (μ-carboxylato)­diiron binding site, employing a combination of Trojan Horse and direct AA coordination approaches . To do so, Borovik and co-workers took advantage of the quaternary structure of Sav, which positions two biotin-binding sites in close proximity and with an intermediary pocket.…”
Section: Catalysis Beyond the Primary Coordination Sphere By Designed...mentioning
confidence: 99%
See 1 more Smart Citation
“…Despite the ubiquitous nature of natural (μ-carboxylato)­diiron enzymes, there are few examples of incorporating such an active site into an ArM due to the difficulty involved in tailoring a binding environment for not one but two metal centers. The de novo Due Ferri (DF) scaffold designed by Lombardi, DeGrado, and co-workers has proven to be extremely valuable for the generation and study of such active sites and is discussed in depth by Pecoraro and co-workers. Recently, the Sav-biotin system was reengineered to form a unique (μ-carboxylato)­diiron binding site, employing a combination of Trojan Horse and direct AA coordination approaches . To do so, Borovik and co-workers took advantage of the quaternary structure of Sav, which positions two biotin-binding sites in close proximity and with an intermediary pocket.…”
Section: Catalysis Beyond the Primary Coordination Sphere By Designed...mentioning
confidence: 99%
“…PCS residues are highlighted as light gray, and SCS in light blue (PDB ID: 6VP1). Atom coloring: N (blue); O (red); S (yellow); Fe (orange).…”
Section: Catalysis Beyond the Primary Coordination Sphere By Designed...mentioning
confidence: 99%
“…Biotinylated dipyridylmethylamine (dpa) ligands containing variable ethyl, propyl, or butyl linkers were used to synthesize the Fe complexes [Fe III (biot-n-dpa)(OH 2 ) 3 ]Cl 3 (n = Et, Pr, Bu), and a series of Sav variants (S112Y, K121Y, and K121A/L124Y) containing tyrosine mutations were selected with the intention of providing a readily visible optical assay for amino acid binding due to Fe III –O Y interactions ( Figure 13 ). 88 Incubation of the complexes in the Sav variants resulted in the observation of an intense blue color (λ max = 605 nm, ε M = 2800 M –1 cm –1 ) indicative of formation of an Fe III –O Y bond for only [Fe III (biot-bu-dpa)]⊂K121A/L124Y-Sav. Binding of the tyrosinate moiety to the Fe III center was further supported by the observation of characteristic phenol ring vibrations and ν(Fe–O Y ) and ν(C–O Y ) modes for Fe III -bound tyrosinate species by resonance Raman spectroscopy.…”
Section: Re-engineering Proteins Into Armsmentioning
confidence: 99%
“…111,153 We note, however, that there are many examples in which synthetic complexes have been inserted into proteins (i.e., artificial metalloenzymes) or synthetic scaffolds (e.g., zeolites), and the environment around the complexes has been shown to play an important role in tuning the chemo-, regio-, site-, and enantioselectivity during catalysis. [154][155][156][157][158][159] High-resolution single-crystal X-ray diffraction has revealed that carbon monoxide, a molecule that inhibits FeMo-cofactor, replaces the belt sulfur atom at 2B position (S2B) in FeMocofactor. 37 The lability of the belt sulfide in FeMo-cofactor inspired the idea to substitute S2B with Se due to its spectroscopic properties by the addition of KSeCN under proton-reducing turnover conditions.…”
Section: Reactivity Of Extracted Femo-cofactormentioning
confidence: 99%